Cost-benefit analysis and water resources management - Brouwer, Roy.; Pearce, David W. (David William) (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2005)
Aims to give an overview of the state-of-the-art in Cost-Benefit Analysis (CBA) in water resources management throughout Europe and North America, along with an examination of current applications.
Includes bibliographical references and index.
oif 16/09/15
Loan
Keywords: Water resources development -- Cost effectiveness -- Case studies